The Effect of Cooperative Computer-Assisted Instructional Package on Upper Basic Students’ Performance in Social Studies - Olokooba, Issa Nasiru (International Journal of Social Learning (IJSL), 2022)
This study investigated the effect of a cooperative computer-assisted instructional package on upper basic Social studies students’ performance in Nigeria. The study adopted a quasi-experimental design. A simple random sampling technique was used to select two intact classes. The two instruments used were Cooperative Computer-Assisted Instructional Package and Social Studies Performance Tests. All hypotheses were tested using Analysis of Covariance at a 0.05 level of significance. The study's findings showed a significant effect of the treatment on Upper Basic students’ performance in Social Studies (F=18.92, P>0.000); there was no significant interaction effect between gender, age, and the treatment on the students’ performance. The study concluded that treatment was more effective in enhancing students’ performance than the conventional method. Accordingly, teachers should be encouraged to use Cooperative Computer-Assisted Instructional Package in teaching students to sustain gender friendliness in classroom situations.